Subducted Front of the Indian Continental Crust Beneath the Tibetan Plateau in the Early Eocene. Issue 10 (30th September 2022) - Long, Xiaoping; Shu, Chutian; Foley, Stephen F.; Wang, Xuan‐Ce; Li, Jie
Abstract: The immense Tibetan Plateau is a masterpiece of the ongoing India–Asia collision. The timing of the collision is a critical parameter to reconstruct the plateau evolution, but has been not well understood yet. Here, we report a newly discovered Eocene (53.8 Ma) shoshonitic intrusion with the input of Indian continental material in the Yangbajing area of the Lhasa Terrane, south Tibet. The reverse 207 Pb/ 206 Pb zoning exhibited by feldspars, the linear isotopic arrays between whole‐rock 187 Os/ 188 Os and 1/ 188 Os, the in‐situ feldspar 208 Pb/ 204 Pb and 206 Pb/ 204 Pb values, and the in‐situ zircon εHf (t) values and δ 18 O values strongly demonstrate a binary interaction process for the generation of the Yangbajing shoshonitic intrusion. Our Os isotopes further illustrate that the interaction process was dominated by recycled crustal melt assimilating minor mantle melt. In addition, different isotopic systems consistently point to an end‐member represented by the underthrust crust slice of Indian continent, which indicates that the Indian lithosphere must have already subducted beneath the Lhasa Terrane at 53.8 Ma. This is also supported by the abrupt isotopic shift toward the enriched values and the composition variation toward the high potassium contents in the subsequent Tibetan magmatism, corresponding to an increasing involvement of the Indian continental crust into the upper plate magmatism. Therefore, the Yangbajing shoshonitic intrusion is one of the earliest known magmatic evidence for the onset of the India–Asia collision. Plain Language Summary: The timing of the ongoing India–Asia collision is a critical parameter to reconstruct the plateau evolution. Here, we report a newly discovered Eocene shoshonitic intrusion with the input of Indian continental material in the Yangbajing area of the Lhasa Terrane, south Tibet. The reverse 207 Pb/ 206 Pb zoning exhibited by feldspars, the linear isotopic arrays between whole‐rock 187 Os/ 188 Os and 1/ 188 Os, the in‐situ feldspar 208 Pb/ 204 Pb and 206 Pb/ 204 Pb values, and the in‐situ zircon εHf (t) values and δ 18 O values strongly demonstrate a binary interaction process for the generation of the Yangbajing shoshonitic intrusion. Our Os isotopes further illustrate that the interaction process was dominated by recycled crustal melt assimilating minor mantle melt. In addition, different isotopic systems consistently point to an end‐member represented by the underthrust crust slice of Indian continent, which indicates that the Indian lithosphere must have already subducted beneath the Lhasa Terrane at 53.8 Ma. Key Points: The early Eocene Yangbajing intrusion in the Lhasa Terrane was generated at 53.8 Ma The intrusion has recorded the subducted front of Indian Plate beneath Tibetan Plateau in the early Eocene The onset of the India–Asia collision was prior to 53.8 Ma